Fabrication and characterization of the electrical properties of phase change materials - Lam, Rachel Wei Qin (2011)
Phase change materials have been extensively studied due to their promising applications in phase change memory. Chalcogenide materials used in these memories can be switched repeatedly between the amorphous and crystalline phase and the corresponding different electrical properties can be used for data storage. Ge2Sb2Te5 (GST) has been one of the most attractive candidates because of its outstanding properties and distinct changes in electrical conductivity between the two phases which can be utilised in phase-change random excess memory (PCRAM).